Propriedades familiares multifuncionais no meio rural nos distritos Arroio Grande e São Valentim - Santa Maria/RS - Rabaiolli, Joel Albino (2013)
This research analyzes the transformations of agrarian sector of Santa Maria RS, perspective of socioeconomic development, with the main objective of studying, evaluating and interpreting these transformations that represent the socio-spatial class called rural. These changes are focused on the optical properties of the multifunctional family of rural class. Even presenting difficulties as access, lack of health services, education, employment, salary and "discomfort" of life, expectations point to new roles that are important in the context of contemporary development to the rural class. To avoid the emptying of the countryside and the imminent collapse of the internal supply, the Brazilian government increased recovery policies and promotion of small properties of class, supporting multiple functions and exploration of cultural knowledge in productive activities. The study of this geographical category adopted the systemic methodology, originated in general systems theory (TGS), crafted by Bertalanffy, the ideas of Morin's system and periodization of time/space based on the Scientific-Technical-Informational period, of Santos, to recognize, evaluate and interpret their dynamics that are in action, as well as the complexity of their actions established in relationships with the city that serves as the consumer market. The use of mixed method allowed to get both: qualitative data and qualitative information enabling to understand the current socio-spatial organization. We conclude that is ample the scope of agricultural and non-agricultural activities developed in the rural class and there are several functions wich identification can be performed by analysis, interpretations and reflections about the subsystems, including its fixed and flows.